Evaluation of Dual Energy X Ray Absorbsiometry and Osteoporosis Risk Factors in 197 Patients - Original Investigation - Şirin Raife Çoban; Canan Gücük Tezel; Afitap İçağasıoğlu; Nesrin Canik Baysal; Ayşen Karabulut; Hatice Şule Taşkıngil (Türk Osteoporoz Dergisi)
Aim: To examine the risk factors for osteoporosis, dual energy X ray absorbsiometry (DXA) measures, dorsolomber radiographics and laboratory analysis of 197 patients which followed in Goztepe Education and Research Hospital Physical Medicine and Rehabilitation Policlinics. Patients and Methods: 197 patients, ages between 37-78, which followed in Physical Medicine and Rehabilitation Policlinics, cross-sectionally evaluated. Patients interrogated about risk factors like life style, calcium-caffeine-alcohol consumption in nutrition, cigarette smoking, age ot menarch, number of births, time of menopause, physical activity levels and their dorsolomber AP-lateral radiograpichs, laboratory analysis and bone mineral density measures with DXA has done. Osteoporosis-osteopenia classification has done by the T score criterias of World Health Organisation. Pearson correlation analysis and ANOVA has used as statistical method. Results: Mean age was 59,24±8,33. Mean body mass index was 26,42±3,99. A significant correlation did not found between life style, nutrition, age of menarch, number of births, early fracture, compression fracture, sunbathe and T scores. A statistically significant correlation has found between age and femur neck T scores; body mass index and lomber-femoral T scores; time of menopause and femur neck T scores (p<0,005). Conclussion: A significant correlation did not found between the minimal risk factors and DXA measures. Age, body mass index and time of menopause has found related to bone mineral density measures. (From the World of Osteoporosis 2007;13:80-2)